2021
DOI: 10.1111/vde.13034
|View full text |Cite
|
Sign up to set email alerts
|

IL‐31 and IL‐31 receptor expression in acute experimental canine atopic dermatitis skin lesions

Abstract: Background -To optimise the interleukin (IL)-31-blocking therapy in atopic dermatitis (AD), an understanding of the chronology in the expression of IL-31 and its receptor (IL-31RA) is needed.Hypothesis/Objectives -(i) To assess the chronological expression of IL-31 in canine AD skin lesions, (ii) to compare it with serum IL-31 levels and macroscopic skin lesion scores, and (iii) to determine the identity of IL-31and IL-31RA-positive cells.Animals -Four atopic dogs sensitised to house dust mites.Methods and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In agreement with our previous study results, 17 we did not observe any significant difference in macroscopic and microscopic skin lesion scores between the LKV and NTC groups at any sampling time points, even though the presence of LKV in the systemic circulation was confirmed by high LKV titres in the LKV-treated group during the entire study period. Our findings further support the proposition that IL-31 is not essential for the induction of acute allergic skin inflammation, which could explain why proactive therapy with LKV is insufficient to prevent AD flares in some dogs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our previous study results, 17 we did not observe any significant difference in macroscopic and microscopic skin lesion scores between the LKV and NTC groups at any sampling time points, even though the presence of LKV in the systemic circulation was confirmed by high LKV titres in the LKV-treated group during the entire study period. Our findings further support the proposition that IL-31 is not essential for the induction of acute allergic skin inflammation, which could explain why proactive therapy with LKV is insufficient to prevent AD flares in some dogs.…”
Section: Discussionsupporting
confidence: 93%
“…13 Furthermore, using the same model, we failed to detect a correlation between the severity of macroscopic inflammatory skin lesions and the amount of infiltrating IL-31-positive cells, further supporting the minimal role of locally released IL-31 in the development of acute flares of allergic skin inflammation. 17 Finally, in our prospective clinical study enrolling client-owned dogs with AD, we observed that half of the dogs treated proactively with LKV monotherapy eventually needed additional anti-allergic medications after two months, indicating other inflammatory mediators, besides IL-31, contribute to flares of AD. 13 The objectives of this study were first to compare the comprehensive transcriptome analysis of a group of dogs treated with LKV (LKV group) with an untreated group of dogs (nontreatment control group: NTC group) to attest our hypothesis that LKV does not majorly affect other cytokine/chemokine production.…”
Section: O R I G I N a L A R T I C L E Cytokine Transcriptome Profili...mentioning
confidence: 86%
“…To identify T -cells, the dog-specific anti-cluster of differentiation 3 (CD3) antibody was used ( 57 ). A recent study has shown that canine CD3 might also be expressed by Th2 cells ( 26 ) which play a pivotal role in AD pathogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…In AD-related hypersensitivity a Th2-polarized lymphocyte response is activated by keratinocytes which produce cytokines (Interleukin [IL]-25 and IL-33), and thymic stromal lymphopoietin (TSLP) which leads to Th2 immune deviation ( 1 , 8 , 18 , 19 ). Activated Th2 cells release IL-31 which stimulate itching by acting on IL-31 receptor A (IL-31RA) expressed on sensory nerve fibers and various immune cells, such as MCs, macrophages, DCs, eosinophils and basophils ( 20 26 ). Macrophages are also stimulated by inflammatory cytokines secreted by keratinocytes, such as granulocyte-macrophage colony-stimulating factor (GM-CSF), tumor necrosis factor-alpha (TNF-α), IL-6 and IL-2 ( 17 , 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aeroallergens such as house dust mite (HDM) are associated to disease severity and total IgE levels in AD ( 32 , 33 ). The relationship between IL-31 and allergens has been poorly characterized and mainly limited to canine models: HDM-sensitized dogs showed IL-31 expression in CD3 + CD4 + T cells in the skin lesions and production of IL-31 by Th2-polarized peripheral blood mononuclear cells (PBMC) stimulated with HDM ( 7 , 34 ). Non-lesional skin from AD patients challenged with HDM induced IL-31 mRNA expression in three out of six HDM allergic patients ( 21 ).…”
Section: Introductionmentioning
confidence: 99%